Food Choice Motives among Workers during COVID-19 Pandemic in Jakarta - Nurulita Aida Rahmasari; Dian Novita Chandra; Helda Khusun (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2022)
Background: COVID-19 pandemic has affected many countries globally. This crisis may influent food choice motives due to the stressful events, prolonged duration of quarantine, lack of in-person contact, fears of infection, and financial loss. Meanwhile, food choice motives remain important as the basic information to form efficient and adaptable dietary intervention to maintain health and well-being, especially among workers to improve their productivity. Purpose: To assess the food choice motives among office workers during the COVID-19 pandemic in Jakarta. Methods: This was an online cross-sectional study on 290 workers aged 25-54 years old in Jakarta. Subjects were recruited through a consecutive sampling method. Food choice motives were assessed using a validated Food Choice Value questionnaire on January-February 2021. Its association with the sociodemographic characteristics was also being analyzed using Spearman, Mann-Whitney, and Kruskal Wallis test to get a complete picture. Results: Safety has become important during this pandemic due to high concern on COVID-19 (p<0.001, r: 0.232). Older worker tend to give more concern on organic (p<0.001, r: 0.254), weight control/health (p<0.05, r: 0.124), and tradition motives (p<0.01, r: 0.161) in choosing food. Meanwhile, access was important to younger (p<0.001, r: -0.205) and single respondents (p<0.01). Married respondents were having significantly higher scores on organic motive (p<0.01). Females were putting more concerned about inconvenience (p<0.01). Tradition motive as the least one reported by the respondents was significantly related to income (p<0.05). Conclusion: Concern on food safety has become the most important due to pandemic conditions. Different motives emerged among different sociodemographic characteristics.